2012
DOI: 10.3168/jds.2010-3912
|View full text |Cite
|
Sign up to set email alerts
|

Estimating efficiency in automatic milking systems

Abstract: Milking data of 34 single automatic milking system (AMS) units on 29 Galician dairy farms were analyzed to determine the system capacity in each farm under actual working conditions. Number of cows, milk yield, milkings per cow per day, actual milking time, rejected milking time, cleaning time, and machine downtime were used to determine the number of cows milked per AMS unit to obtain the optimal values of milkings per cow and milk production. Multiple linear regression data analysis was used to model the lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
62
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 10 publications
11
62
3
2
Order By: Relevance
“…The present study found more MCD in summer and winter months and in the group of older cows (multiparous). In investigating mean MCD, Carlström et al (2013) and Castro et al (2012) obtained results similar to those of the present study, whereas Gygax et al (2007) obtained a slightly lower result, at 2.5 (range: 0.8 to 3.9 per cow). A higher MCD value in relation to the one obtained in this study was reported by Deming et al (2013; 2.8 ± 0.4 times a day), and Madsen et al (2010) reported on average as many as three milkings per day.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The present study found more MCD in summer and winter months and in the group of older cows (multiparous). In investigating mean MCD, Carlström et al (2013) and Castro et al (2012) obtained results similar to those of the present study, whereas Gygax et al (2007) obtained a slightly lower result, at 2.5 (range: 0.8 to 3.9 per cow). A higher MCD value in relation to the one obtained in this study was reported by Deming et al (2013; 2.8 ± 0.4 times a day), and Madsen et al (2010) reported on average as many as three milkings per day.…”
Section: Discussionsupporting
confidence: 87%
“…Already prior studies on AMSs (Sitkowska et al, 2013) demonstrated a statistically significant effect of factors on the milk yield of cows milked by an AMS, which has been confirmed in this study. Castro et al (2012) found that in Spanish herds, the average number of cows per robot was about 52.7, which was significantly less than in the Polish herds studied. Castro et al (2012), Edwards et al (2014) and Løvendahl and Chagunda (2011) found that the mean MY from cows during milking by an AMS was about 10.70 kg, which is similar to the figure found in this present study.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Continuing with the study initiated by our research group concerning the efficiency of AMS in dairy farms in northwestern Spain (Castro et al, 2012), data was collected by conducting an in-person survey that covered all the farm owners within the Autonomous Community of Galicia that had AMS installed in their farms. Galician dairy farms contributed with 37.9% of the total Spanish cow milk production in 2010.…”
Section: Area Of Studymentioning
confidence: 99%